1989
DOI: 10.1172/jci114046
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 gene expression in normal and neoplastic B cells.

Abstract: In the present report we demonstrate that the IL-6 gene is expressed in anti-Ig-activated and neoplastic B cells. After activation with anti-Ig, splenic B cells rapidly expressed mRNA with peak expression occurring at 4 h and declining rapidly thereafter. In an attempt to exclude that the IL-6 mRNA expression was in non-B cells, T cells and monocytes were extensively depleted. In this highly purified B cell population, IL-6 mRNA was retained, whereas the expression of the T cell-and monocyte-restricted CD2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(53 citation statements)
references
References 32 publications
1
52
0
Order By: Relevance
“…Earlier studies have suggested that IL-6 is involved in the pathogenesis of several diseases including Hodgkin's disease [13,14]. In our study, IL-6 was estimated in the serum of healthy controls as well as patients.…”
Section: Discussionmentioning
confidence: 66%
“…Earlier studies have suggested that IL-6 is involved in the pathogenesis of several diseases including Hodgkin's disease [13,14]. In our study, IL-6 was estimated in the serum of healthy controls as well as patients.…”
Section: Discussionmentioning
confidence: 66%
“…Two B7-related molecules have been cloned from man and mouse: B7-I (Freeman et al, 1989, 1991) and B7-2 (Freeman et al, 1993a, 1993b) or B7-0 (Azuma et al, 1993. These molecules are members of the immunoglobulin superfamily (IgSF), comprising a V(ariab1e)-like and a C(onstant)-like domain in their extracellular regions.…”
mentioning
confidence: 99%
“…As previously reported, IL-6 is one of the main growth and survival factors for MM cells, which can activates some signaling pathways; for instance, MAPK and the (PI-3K)/Akt signaling cascades mediate IL-6-induced MM cell growth and survival. [27][28][29][30][31][32] Most recently, some studies have shown that NF-κβ activation in the regulation of IL-6 transcription is produced in the BMSCs after MM cell adhesion. Furthermore, stromal cells can induce some antiapoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%